2013
DOI: 10.1371/journal.ppat.1003555
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Models of the Dose-Response and Time Course of Inhalational Anthrax in Humans

Abstract: Anthrax poses a community health risk due to accidental or intentional aerosol release. Reliable quantitative dose-response analyses are required to estimate the magnitude and timeline of potential consequences and the effect of public health intervention strategies under specific scenarios. Analyses of available data from exposures and infections of humans and non-human primates are often contradictory. We review existing quantitative inhalational anthrax dose-response models in light of criteria we propose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…This estimate was derived from an exposure scenario of 11,000 inhaled B. anthracis spores, a dose proposed to cause infection in 50% of susceptible nonvaccinated individuals (ID 50 ). Lower estimated exposure doses had associated longer periods of incubation (34). Historically, the estimated exposure levels in high-risk industrial environments were estimated at 21 to 2,100 infectious particles per 8-h day (35,36), significantly lower than those proposed by Toth et al A systematic review and analysis of 82 inhalation anthrax cases by Holty et al indicated that postincubation, the mean time from symptom onset to death was 4.8 days (31).…”
Section: Discussionmentioning
confidence: 95%
“…This estimate was derived from an exposure scenario of 11,000 inhaled B. anthracis spores, a dose proposed to cause infection in 50% of susceptible nonvaccinated individuals (ID 50 ). Lower estimated exposure doses had associated longer periods of incubation (34). Historically, the estimated exposure levels in high-risk industrial environments were estimated at 21 to 2,100 infectious particles per 8-h day (35,36), significantly lower than those proposed by Toth et al A systematic review and analysis of 82 inhalation anthrax cases by Holty et al indicated that postincubation, the mean time from symptom onset to death was 4.8 days (31).…”
Section: Discussionmentioning
confidence: 95%
“…The inhalational ID1 (1% infectious dose) of Bacillus anthracis is estimated to be 160 spores (95% confidence interval, 100 to 250 spores) (19). The level of potential exposure for sampling personnel within these parameters, in the absence of respiratory protective equipment (RPE), would clearly pose an unacceptable risk.…”
Section: Discussionmentioning
confidence: 99%
“…¶360 spores is a dosage estimated to have occurred during the 1979 Sverdlovsk (USSR) anthrax event ( 13 ). One spore represents the minimum possible infectious dose, and 8,000 is a plausible high dose ( 14 ). #Cannot exceed the value of the Epidemic-Curve model “Population size of the impacted jurisdiction” parameter.…”
Section: Methodsmentioning
confidence: 99%